2021
DOI: 10.5334/gh.920
|View full text |Cite
|
Sign up to set email alerts
|

Global Burden of Aortic Aneurysm and Attributable Risk Factors from 1990 to 2017

Abstract: Background: To date, our understanding of the global aortic aneurysm (AA) burden distribution is very limited. Objective: To assess a full view of global AA burden distribution and attributable risk factors from 1990 to 2017. Methods: We extracted data of AA deaths, disability-adjusted life years (DALYs), and their corresponding age-standardized rates (ASRs), in general and by age/sex from the 2017 Global Burden of Disease (GBD) study. The current AA burden distribution in 2017 and its changing trend from 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…In 2019, the mortality rate due to AA in males was almost triple that of females, in line with global data [ 11 , 13 ], possibly due to risk factor exposure in men, such as smoking, hypertension, and hypercholesteremia [ 22 ]. It was reported that the sex differences in aortic aneurysm formation were influenced by sex hormones [ 23 ].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In 2019, the mortality rate due to AA in males was almost triple that of females, in line with global data [ 11 , 13 ], possibly due to risk factor exposure in men, such as smoking, hypertension, and hypercholesteremia [ 22 ]. It was reported that the sex differences in aortic aneurysm formation were influenced by sex hormones [ 23 ].…”
Section: Discussionsupporting
confidence: 69%
“…The mortality rate increased consistently with age in both males and females [ 12 , 13 ]. Meanwhile, in line with the global trend [ 13 ], the percentage of elderly deaths from AA was growing (Supplementary Figure 2 ), and the population aged 60-80 sustained the highest YLLs due to AA in 2019, a shift from the most affected age group in 1990, aged 55-75, and this shift was mainly caused by the increased longevity of the population [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as observed by the most recent analysis using 1990–2017 Global Burden of Disease Study (GBD) data, the decreasing mortality trend due to AA in the past few years has begun to plateau worldwide. AA-related mortality has increased in many regions, such as Central Asia, North Africa, and Central and Eastern Europe [ 6 , 7 ]. As an important cardiovascular disease, the global burden of AA may further increase due to population ageing and the proliferation of other important behavioural and metabolic risk factors, such as smoking, hypertension, non-alcoholic fatty liver disease, and hyperlipidaemia, especially in developing countries [ 8–10 ].…”
Section: Introductionmentioning
confidence: 99%